A new algorithm shows superior ability to discriminate liver fibrosis stages in chronic hepatitis C. Issue 10 (14th July 2021) - Varchetta, Stefania; Mele, Dalila; D'Ambrosio, Roberta; Perbellini, Riccardo; Lombardi, Andrea; Rojas, Angela; Paolucci, Stefania; Baldanti, Fausto; Oliviero, Barbara; Mantovani, Stefania; Tinelli, Carmine; De Silvestri, Annalisa; et al.
Abstract: Previous evidence suggests that sialic acid‐binding Ig‐like lectin 7 (Siglec‐7) protein is significantly increased in patients with chronic hepatitis C virus (HCV) infection and directly correlates with clinical parameters of liver inflammation and fibrosis. The aim of this study was to determine the diagnostic value of Siglec‐7 as a non‐invasive tool to assess liver fibrosis in patients with chronic hepatitis C in a cross‐sectional study. Serum levels of Siglec‐7 were retrospectively tested in 1007 consecutive patients with chronic HCV infection recruited at three different European sites and data examined by the 'imperfect gold‐standard' statistical analysis. Liver stiffness obtained by transient elastography (TE) was considered the standard reference. Liver fibrosis was staged according to published cut‐offs of liver stiffness measurement by TE. Accuracy of detection of liver fibrosis stage was not increased by Siglec‐7 alone. However, we developed a new index (SiGAP) including Siglec‐7, γ‐glutamyl transferase, age and platelet count which showed increased sensitivity and specificity in predicting fibrosis compared with APRI or FIB4 indices. The AUROC of SiGAP for the diagnosis of significant (≥F2) and advanced liver fibrosis (≥F3) showed significantly higher values than those of APRI and FIB‐4. Siglec‐7 may be useful as a complementary tool to assess liver fibrosis stage in patients with chronic hepatitis C when included in a specifically designed algorithm, which showed high level of accuracy in the detection of F2 and F3 fibrosis stage.